Development of speed-strength endurance of girls aged 9-13 - Feroyan, E. (Національний технічний університет «Харківський політехнічний інститут», 2023)
The aim of the study was to study and identify the features of the development of speed-strength endurance and the body's adaptation to it in girls 9-13 years old, involved in sports and not involved in sports. Fifteen young swimmers (main group) took part in the process of dynamic observations. The study lasted three academic years. Speed-strength endurance (300 m run), lactate, heart rate, blood pressure were determined. Compared with the group of girls who made up the control group. The speed of running for 300 m according to the average values in the main group corresponded to 4,40 ± 0,22 s, and in the control group – 3,98 ± 0,33 s, or 10,6% was lower. When analyzing the process of anaerobic metabolism, it was found that the level of lactate in the blood of the girls of the main group was significantly higher (7,977 ± 2,33 mmol/l) compared to the girls of the control group (5,335 ± 2,37 mmol/l), the difference in lactate at the first stage of the survey was 33,1% (p<0,05). The data obtained made it possible to conclude that the selected schoolgirls in the main group had an advantage in the development of the process of anaerobic metabolism of carbohydrates, in particular muscle glycogen, compared to the group of girls not involved in sports, which served as the basis for the development of their more significant speed-strength endurance.
Keywords: young athletes and athletes; speed-strength endurance; lactate; adaptation; юні спортсмени і легкоатлети; швидкісно-легкова витривалість; лактат; адаптація